Lupus nephritis as a specific clinical and immunological phenotype of systemic lupus erythematosus - E. A. Aseeva; A. M. Lila; S. K. Soloviev; S. I. Glukhova (Современная ревматология, 2022)
Lupus nephritis (LN) is the leading cause of death in systemic lupus erythematosus (SLE), so its early detection and treatment is of utmost importance. Features of the onset, clinical signs, certain morphological classes, as well as more aggressive therapy make it possible to assign SLE with LN to a distinct disease phenotype.Objective: to characterize the clinical, immunological and morphological features of the SLE phenotype with a predominant kidney involvement based on a comparative analysis of patients with LN and without LN.Patients and methods. The study included 400 patients with SLE who met the 2012 SLICC criteria and were hospitalized to V.A. Nasonova Research Institute of Rheumatology from 2013 to 2021. The diagnosis of LN was established in 192 (48%) patients, of which in 82 (43%) it was confirmed by pathological study of kidney biopsy specimens (the SLE group with LN). In 208 (52%) patients, no kidney damage was observed, and they constituted the SLE group without LN.All patients underwent a standard examination with an assessment of disease activity according to the SLEDAI-2K index, irreversible changes in organs according to the SLICC damage index, immunological disorders, clinical and biochemical blood tests, urinalysis according to unified methods, glomerular filtration rate, as well as pathological examination of kidney biopsy specimens for confirmation of LN in the presence of an appropriate clinical picture. In patients of both groups, a comparative study of the main clinical, laboratory, immunological manifestations of SLE, the features of the disease onset, its first clinical signs, possible trigger factors, and the drugs used was carried out.Results and discussion. In the LN group, insolation was more likely to trigger the development of SLE than in the group without LN (respectively, in 26% and 13% of cases; p=0.007). In turn, SLE without kidney damage more often than SLE with LN debuted during pregnancy or after childbirth.The first signs of the disease in almost 40% of patients with LN were proteinuria and/or changes in urinary sediment, edema, increased blood pressure, the development of LN in some cases was preceded by polyarthritis or combined lesions of the skin and joints, but no later than 6 months, signs of kidney damage appeared. In the SLE group without LN, polyarthritis (in 33%), combined lesions of the skin and joints (in 26%), and Raynaud's syndrome (in 16%; p <0.0001) were more often observed at the onset. In patients with LN, erythematous lesions of the facial skin ("butterfly", in 42%), serositis (exudative pleuritis — in 44%, pericarditis — in 46%, ascites and hydrothorax — in 5%; p<0.0001), as well as hematological disorders such as anemia (in 63%), leukopenia (in 49%) and thrombocytopenia (in 42%) were present more frequently. With the development of LN, an acute course and high activity of the disease occurred significantly more often. In the study of immunological parameters in the group without LN, lupus anticoagulant (in 6%) and antibodies to SS-A/Ro and SS-B/La (in 18 and 9% of patients, respectively) were detected significantly more often, while in the LN group — hypocomplementemia (in 81%; p<0.0001). Therapy also differed significantly: patients with LN received higher doses of glucocorticoids (p<0.0001), mycophenolate mofetil, and cyclophosphamide.Conclusion. SLE with LN can be considered a distinct disease phenotype with a set of characteristics (clinical and laboratory parameters, response to therapy, prognosis) that distinguish it from other SLE variants.